Социология: исторические истоки и современные трансформации - Кутуев, П. (Iнститут соціології НАН України, 2009)
The chapter seeks to identify the historical roots of sociological knowledge and its contemporary transformations. The chapter traces the origins of sociology as a separate discipline. Sociology's subject-matter is also discussed. Based on new publications utilizing archival data, the chapter claims that the term "sociology" was suggested by Emmanuel Joseph Sieyès (1748 -1836) in his manuscript circa 1780. The chapter makes extensive use of Max Weber's insights into the nature of sociology as an empirical discipline ordering the chaotic universe according to ultimate values of a researcher. The chapter also advocates the centrality of classical thinkers and their texts for the discourse of contemporary sociology. The chapter suggests Imre Lakatos' methodology of research programs as a tool for grasping the evolution of sociological knowledge. The texts discusses how sociology was transforming under the impact of global social transformations, while contributing to them. The sources of sociology's original Eurocentrism are identified. The chapter also discusses the tasks of sociology today and outlines the prospects of its development.